2020
DOI: 10.1038/s41598-020-66084-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes Mellitus and Its Associated Factors in Bangladesh: Application of Two-level Logistic Regression Model

Abstract: this study intends to explore the prevalence of diabetes mellitus (DM) and its associated factors in Bangladesh. the necessary information was extracted from Bangladesh Demographic and Health Survey (BDHS) 2011. In bivariate analysis, Chi-square test was performed to assess the association between selected covariates and diabetes status. A two-level logistic regression model with a random intercept at each of the individual and regional level was considered to identify the risk factors of DM. A total of 7,535 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 89 publications
8
52
1
Order By: Relevance
“…As found in the previous literatures [29,54], present study found that people involved in any type of work were at reduced risk of diabetes and comorbidity. Involving in work increases the physical activity and several studies found a negative association between moderate/higher levels of physical activities and chronic diseases [55,56].…”
Section: Discussionsupporting
confidence: 86%
“…As found in the previous literatures [29,54], present study found that people involved in any type of work were at reduced risk of diabetes and comorbidity. Involving in work increases the physical activity and several studies found a negative association between moderate/higher levels of physical activities and chronic diseases [55,56].…”
Section: Discussionsupporting
confidence: 86%
“…In the current study, we noticed that the number of females who participate in the study slightly exceeds the number of males, and this may be related to the fact that females are generally more than males in our country [19] or were more interested in participation rather than males. Even there was no definite difference between both sexes in the prevalence of DM, previous studies found a significant increase in the prevalence of DM among women relative to men, and this also can explain the higher percentage of females in our sample [20,21]. The majority of the patients were overweight and obese because it is a known risk factor for type 2 DM.…”
Section: Discussioncontrasting
confidence: 59%
“…The physical activity variable was not directly available in BDHS, 2017-18. For this reason, the occupation type was used as a proxy variable for measuring physical activity [24]. A respondent was considered physically active if his/her work liability includes physical activity related works; otherwise they were physically inactive [24].…”
Section: Risk Factorsmentioning
confidence: 99%
“…For this reason, the occupation type was used as a proxy variable for measuring physical activity [24]. A respondent was considered physically active if his/her work liability includes physical activity related works; otherwise they were physically inactive [24]. The physically active group consisted of farmer; agricultural worker; sherman; cattle raising, poultry raising; home based manufacturing; rickshaw driver, road building, brick breaking, construction worker; domestic servant; and factory worker, on the contrarily, the physically inactive group consisted of not working; land owner; carpenter, tailor; doctor, nurse, dentist, lawyer, accountant, teacher; businessman; unemployed/student; and retired person.…”
Section: Risk Factorsmentioning
confidence: 99%